Effect of Environmental Factors on Physicochemical Properties of Castor Oil (Ricinus communis L.) - A Alirezalu; K Alirezalu; G Karimzadeh; R Omidbaigi (Institue of Medicinal Plants, ACECR, 2011)
Background: Castor bean (Ricinus communis L.) is one of the most important medicinal plants that used in pharmaceutical, cosmetics and hygienic industries in most of developed countries. The versatile application of castor oil in different industry and recently in food science because of its unique physicochemical properties has led castor oil to be the focus of abundant research projects. Objective: The purpose of this study was to determine, the impact of 7 different climatic conditions in Iran on the castor oil production by castor bean from the standpoints of the quality, oil content and physicochemical properties of castor oil. Methods: Seeds were harvested after ripening and were transferred to laboratory for measurement of physicochemical properties. Tests were included, measurement of either chlorophyll content by spectrophotometer, or refractive index by refractometer, or moisture oil, saponification value, acid value, peroxide value and iodine value by AOCS standards. Results: The results showed that climatic factors had significant effects on oil content, moisture content, acid value, peroxide value, iodine value, chlorophyll content and saponification value. With the analyzed oil samples, oil content, humidity, refractive index, chlorophyll content, saponification value, iodine value, acid value, and peroxide value were respectively determined as 35% - 51%, 0.3% - 1.14%, 1.404 - 1.426, 0.16 - 0.4 mg Phenophytin/ kg Oil, 164 - 1/79 mg KOH/g Oil, 75 - 86 g I2/100 g Oil, 0.29 - 0.6 mg NaOH/g Oil, 0 - 0.5 meq O2/kg oil. Conclusion: Results showed that Urmia, Nazarlu and Marand can be considered for medicinal castor bean plant cultivation for high quality of oil.